PERANCANGAN SISTEM MONITORING JARAK JAUH PADA SMART AGRICULTURE SYSTEM - Abie Pangestu; Ulinnuha Latifa; Lela Nurpulaela (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2023)
The seeding process is the process of making seeds into seedlings that are ready to plant.The seeding process serves to produce quality seedlings and serves to reduce the death that occurs in the seeds.To produce quality seedlings, favorable environmental conditions are needed to maintain factors that affect the results of the seeding process.Internet of Things technology in agriculture can help in monitoring crop growth, monitoring can be done anywhere and anytime.Monitoring plant growth conditions is done by sending data from microcontrollers, namely NodeMCU ESP32 to the Database, namely Google Firebase and then the android application takes the data in the database and displays the data processing results.Creating a plant growth monitoring application that has a user-friendly design and a good level of data delivery accuracy is expected to be able to improve the quality of rice seedlings.The use of Internet of Things transmission for the transmission of data from microcontrollers to applications was declared successful.The data sent has an accuracy rate of 100% of each data sent.Applications or user interfaces are able to provide important information for users to more easily understand products and about sowing rice.The application is able to display real-time data transmitted by microcontrollers accurately.